The Performance of Clay-based Biomass Briquette Stove with Three Geometry Shape Variations - Suluh, Sallolo; Yusuf, Mohammad; Fauzi, Muhammad Irsyad; Amaliyah, Novriany; Djafar, Zuryati; Piarah, Wahyu Haryadi (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Biomass briquette stove is a cooking tool that is still widely used by the people of the interior of South Sulawesi. Even in urban areas, it is not uncommon to find their use because of the ease of obtaining briquettes and its relatively good efficiency. This study aims to determine the best performance of a biomass stove from three types of clay material stove shapes in different configurations of geothermal variations. The three variations of the geometric shape of the stove are cylindrical, rectangular and hexagonal using biomass material from coconut shell charcoal in the shape of a honeycomb with an inner diameter of 15 mm and an outer diameter of 65 mm and a height of 45 mm. The uniqueness of this stove is the addition of a sleeve diameter of 180mm in the stove's combustion chamber as heat insulation so that the combustion process in the combustion chamber can be more perfect. The test results show that the presence of a flat surface on the stove wall will accelerate heat loss compared to the cylindrical surface. This is in line with the results which show that the highest rate of heat loss occurs in a rectangular shape, then a six-square shape, and the last is a cylindrical shape. Furthermore, it can be concluded that the cylindrical stove is the superior of the two in terms of flame temperature, ability to boil water and thermal efficiency of 798Ã‚Â°C, 30 liters and 73.66%, respectively.